2013
DOI: 10.1371/journal.pcbi.1003038
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Protein Aggregation in Escherichia coli Is Governed by Diffusion and Nucleoid Macromolecular Crowding Effect

Abstract: Aggregates of misfolded proteins are a hallmark of many age-related diseases. Recently, they have been linked to aging of Escherichia coli (E. coli) where protein aggregates accumulate at the old pole region of the aging bacterium. Because of the potential of E. coli as a model organism, elucidating aging and protein aggregation in this bacterium may pave the way to significant advances in our global understanding of aging. A first obstacle along this path is to decipher the mechanisms by which protein aggrega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
156
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 66 publications
9
156
0
Order By: Relevance
“…Restriction of aggregates to the pole was also observed during treatment with substances disrupting the protein motive force, suggesting an energy independent process of aggregation [20]. Energy-independent polar localization was also confirmed by others [30] but also convincing opposite results were obtained [15]. Thus, it is not absolutely clear if active ATP-dependent transport of smaller particles is required or if the fluidizing properties of active metabolism are responsible for the polar preference of protein aggregates [16].…”
Section: Cellular Formation Of Ibsmentioning
confidence: 80%
See 2 more Smart Citations
“…Restriction of aggregates to the pole was also observed during treatment with substances disrupting the protein motive force, suggesting an energy independent process of aggregation [20]. Energy-independent polar localization was also confirmed by others [30] but also convincing opposite results were obtained [15]. Thus, it is not absolutely clear if active ATP-dependent transport of smaller particles is required or if the fluidizing properties of active metabolism are responsible for the polar preference of protein aggregates [16].…”
Section: Cellular Formation Of Ibsmentioning
confidence: 80%
“…There are claims that transport of aggregates to the poles is energy-driven as studies on reassembly of pressure dissociated IBs revealed that confinement to the pole is caused by the presence of the nucleoid but reassembly of smaller aggregates into large IBs does not occur in energy and nutrient depleted cells [16]. However, there are also reports stating that exclusion of aggregates from mid-cell to the pole is energy-free, and simply results from nucleoid exclusion [17,20,[28][29][30]. Restriction of aggregates to the pole was also observed during treatment with substances disrupting the protein motive force, suggesting an energy independent process of aggregation [20].…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulations are often integrated with experiments performed in vivo to provide a microscopic interpretation of cellular phenomena (Hihara et al 2012;Coquel et al 2013;Di Rienzo et al 2014;Earnest et al 2017). Although powerful to predict macromolecule behavior, this technique, defined as the Bcomputational microscope^by Schulten (Lee et al 2009), has some limitations (Takada 2012;Piana et al 2014;Ivani et al 2016;Song et al 2017;Wang et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies of subcellular localization of RNAs and proteins have induced the development of spatiotemporal models of gene expression. A few available models are focused on protein aggregation and nucleoid occlusion [19][20][21]. Protein localization near the transcription region was described as a consequence of diffusion within and exchange between the condensed chromosomal DNA and an extrachromosomal area [9,22].…”
Section: Introductionmentioning
confidence: 99%